Efficacy and safety of injection with poly‐L‐lactic acid compared with hyaluronic acid for correction of nasolabial fold: a randomized, evaluator‐blinded, comparative study. (1st March 2015) - Hyun, M. Y.; Lee, Y.; No, Y. A.; Yoo, K. H.; Kim, M. N.; Hong, C. K.; Chang, S. E.; Won, C. H.; Kim, B. J.
Summary: Background: Hyaluronic acid (HA) fillers and poly‐L‐lactic acid (PLA) fillers are frequently used to correct facial wrinkles. Aim: To compare the efficacy and safety of a novel injectable poly‐L‐lactic acid (PLA) filler and a well‐studied biphasic HA filler for the treatment of moderate to severe nasolabial folds. Methods: In this multicentre, randomized, evaluator‐blinded, comparative study, subjects were randomized for injections with PLA or HA into both nasolabial folds. Efficacy was determined by calculating the change in Wrinkle Severity Rating Scale (WSRS) relative to baseline. Local safety was assessed by reported adverse events. Results: At week 24, mean improvement in WSRS from baseline was 2.09 ± 0.68 for the PLA side and 1.54 ± 0.65 for the HA side. Both injections were well tolerated, and the adverse reactions were mild and transient in most cases. Conclusions: PLA provides noninferior efficacy compared with HA 6 months after being used to treat moderate to severe nasolabial folds.